PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Yuliyanti, Leni (Universitas Pendidikan Indonesia, 2014)
The objective of this research was to discover the effects of Good Corporate Governance(CGC) and Corporate Social Responsibility (CSR) disclosure on firm value. This studyemployed a descriptive-verifying method. The population in this study was the companies listedin the IICGP ranking, selected through purposive sampling technique. The data collectiontechnique utilized documentation study with descriptive analysis technique and classicalassumption tests; F test and t test. The results of the study demonstrated that GCG gavesignificant positive effect on firm value, CSR disclosure gave significant positive effect on firmvalue, as well as GCG and CSR disclosure gave significant positive effect on firm value.